2020
DOI: 10.5812/gct.101963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Intensity Interval Training on Apoptotic Gene Expression in Rat Myocardial Tissue

Abstract: Background: Excessive apoptosis in the myocardium contributes to the pathogenesis of heart disease. Evidence indicates that high-intensity interval training (HIIT) can alter myocardial apoptosis-related signaling. Objectives:The purpose of the study was to investigate the effect of 12 weeks of HIIT on some indices of apoptosis, including Bcl-2, Bax, and caspase-3 in the myocardial tissue of male rats. Methods: Thirty male Wistar rats (age range: 8 -10 weeks) were randomized into three groups, including sham (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In the meantime, Bax and Bcl2 proteins are involved in the formation of apoptosis and mitochondrial apoptotic signaling as the main proteins. Increasing Bcl2 and, consequently, decreasing the Bax/ Bcl2 ratio is one of the most important factors to avoid mitochondrial membrane damage as well as to prevent apoptosis (20). To date, no studies have been conducted to investigate the effect of HIIT training on cardiac apoptosis in obese subjects, and the results obtained by similar studies on non-obese subjects and other tissues are often contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, Bax and Bcl2 proteins are involved in the formation of apoptosis and mitochondrial apoptotic signaling as the main proteins. Increasing Bcl2 and, consequently, decreasing the Bax/ Bcl2 ratio is one of the most important factors to avoid mitochondrial membrane damage as well as to prevent apoptosis (20). To date, no studies have been conducted to investigate the effect of HIIT training on cardiac apoptosis in obese subjects, and the results obtained by similar studies on non-obese subjects and other tissues are often contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…The OC group was excluded from participating in any training intervention until the end of the course. The OT group was subjected to a high-intensity interval training program performed 5 sessions per week over 12 weeks (Table 1) (20). The treadmill speed was increased by five percent each week to meet the principle of overload.…”
Section: High-intensity Interval Training Protocolmentioning
confidence: 99%
“…Shin Fujimaki et al reported that chronic running activated the satellite cells in the diabetic mice, improving the Wnt signaling pathway (28). Pourrazi et al showed that by affecting Wnt signaling, exercise activity improved the process of muscle mass loss due to dietary restriction (29). In this regard, some reports have suggested that GSK-3β can either directly activate the phosphorylation of pre-apoptotic proteins such as Bax or increase the expression of Bim (30,31).…”
Section: Discussionmentioning
confidence: 99%